2012 Florida Constitutional Amendment 11: Additional Homestead Exemption; Low-Income Seniors Who Maintain Long-Term Residency on Property; Equal to Assessed Value - Rodney L. Clouser (EDIS)
In addition to 2012 being a presidential election year, Florida voters also will be asked to vote on a number of proposed amendments to their state constitution. Many voters remain either unaware or less informed regarding the effects and impacts of the proposed constitutional amendments. This document is one of a series of 6 fact sheets that was written by Rodney L. Clouser and published by the UF Department of Food and Resource Economics, July 2012.